Methods for improving energy performance of single-family buildings in Poland’s climatic conditions - Jędrzejuk, Hanna; Jaworski, Maciej; Chwieduk, Michał (International Conference “Environmental Engineering”, 2017)
The effect of standard means of thermal upgrading of buildings on energy performance indices is studied in the paper. The following was considered: improving thermal performance of the envelope (walls, roof, floors over unheated cellars or ground-floor slabs, windows, and doors); using exterior blinds during heating and cooling seasons; using heat recovery (recuperation) in a forced ventilation system; reducing the ventilation air flow rate; and improving air-tightness of a building. The calculations were performed for a number of variants. Seven locations in Poland were selected based on outdoor climate conditions. Various standards of thermal performance of the building envelope, internal heat capacities, and ventilation rates were applied. Variations in internal heat gains, depending on the presence of occupants (heat gains from occupants and from lighting) were considered. Due to a dynamic nature of the energy processes that take place in a building, the simplified hourly method 5R1C was used in calculations. It was verified whether single-family buildings constructed in a way that is typically found in Poland, i.e. buildings with very high heat capacity and equipped with a forced ventilation system, can meet more stringent energy performance requirements.
Keywords: energy-efficient buildings; thermomodernization; single family buildings